Nanograin study of polycrystalline ceramics based on cerate-zirconate via two-step sintering / Azliana Ramli … [et al.] - Ramli, Azliana; Osman, Nafisah; Safian, Suhaida Dila; Abu Talib, Ibrahim (Research Management Institute (RMI), 2015)
Increasing in the energy demand lead the world to focus on an alternative energy conversion technologies. Solid oxide fuel cells (SOFCs) offer more efficiency in conversion of chemical energy in fuels into electricity. There is worldwide interest in reducing the operating temperature of SOFCs to 500-700°C for long-term stability and lower cost. Proton conducting solid oxide fuel cells (PCFCs) are under intense study due to their lower operating temperature < 800°C compared to the conventional oxygen ion conducting solid oxide fuel cells [1]. Cerate-zirconate ceramics with perovskite structure of ABO3 is one of the promising candidates as solid electrolyte for PCFCs applications due to its low activation energy for proton conduction. A better understanding of proton conduction in this material requires a systematic study on the role of synthesizing process and heat treatment in controlling the material's microstructure…